2016
DOI: 10.1016/j.nut.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged maternal separation induces undernutrition and systemic inflammation with disrupted hippocampal development in mice

Abstract: Objective Prolonged maternal separation (PMS) in the first two weeks of life has been associated with poor growth with lasting effects in the brain structure and function. This study aimed to investigate whether PMS-induced undernutrition could cause systemic inflammation and changes in nutrition-related hormonal levels, affecting hippocampal structure and neurotransmission in C57BL/6J suckling mice. Methods This study assessed mouse growth parameters coupled with IGF-1 serum levels. In addition, leptin, adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
(79 reference statements)
4
11
0
Order By: Relevance
“…The distance to escape, which showed a trial-dependent deficit in performance on the Barnes maze induced by maternal separation, could be a sign of abnormal development of the hippocampus as one of the main sites involved in spatial memory in the brain [ 3 , 13 ]. Several reports confirm that maternal separation results in long-term changes in the morphology of the cognitive brain structures, such as a reduction in the hippocampal volume and size of the pyramidal and granular layers [ 32 ], a reduction in the number of neurons in the dentate gyrus [ 33 ] and a reduction in the CA1 pyramidal cell layer and CA3 area and volume [ 8 ], which could lead to memory impairment [ 34 , 35 ]. Figueiredo et al [ 8 ] showed that pups have a slower linear growth and poorer weight gain following prolonged maternal separation as compared to the controls, which could be a characteristic of under-nutrition and could also be the cause of changes in the pups’ hippocampus morphology and function [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance to escape, which showed a trial-dependent deficit in performance on the Barnes maze induced by maternal separation, could be a sign of abnormal development of the hippocampus as one of the main sites involved in spatial memory in the brain [ 3 , 13 ]. Several reports confirm that maternal separation results in long-term changes in the morphology of the cognitive brain structures, such as a reduction in the hippocampal volume and size of the pyramidal and granular layers [ 32 ], a reduction in the number of neurons in the dentate gyrus [ 33 ] and a reduction in the CA1 pyramidal cell layer and CA3 area and volume [ 8 ], which could lead to memory impairment [ 34 , 35 ]. Figueiredo et al [ 8 ] showed that pups have a slower linear growth and poorer weight gain following prolonged maternal separation as compared to the controls, which could be a characteristic of under-nutrition and could also be the cause of changes in the pups’ hippocampus morphology and function [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports confirm that maternal separation results in long-term changes in the morphology of the cognitive brain structures, such as a reduction in the hippocampal volume and size of the pyramidal and granular layers [ 32 ], a reduction in the number of neurons in the dentate gyrus [ 33 ] and a reduction in the CA1 pyramidal cell layer and CA3 area and volume [ 8 ], which could lead to memory impairment [ 34 , 35 ]. Figueiredo et al [ 8 ] showed that pups have a slower linear growth and poorer weight gain following prolonged maternal separation as compared to the controls, which could be a characteristic of under-nutrition and could also be the cause of changes in the pups’ hippocampus morphology and function [ 36 ]. In contrast to the STR group, assessment of the strategy used to reach the escape box in the non-STR group revealed an increase in the frequency of using the direct strategy and a reduction in the use of the random strategy over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association between early adversity exposure and inflammation has been well-documented (See Baumeister et al, 2016; Miller et al, 2011 for review), the vast majority of studies have assessed early adversity exposure across multiple phases of child development, typically spanning infancy through adolescence. Similarly, rodent work focusing on the effects of early adversity on inflammatory markers has typically induced stress during postnatal days 2–20 (Figueiredo et al, 2016; O’Mahony et al, 2009; O’Malley et al, 2011; Roque et al, 2015). Nevertheless, there are studies hinting that the inflammatory consequences of adversity during development may vary as a function of timing of adversity exposure and these associations warrant further investigation.…”
Section: 1 Theoretical and Empirical Support For Examining The Rolementioning
confidence: 99%
“…Both the repeated maternal separation (RMS), such as the separation for 30 min or a few hours for several days or weeks, and the one time maternal separation (MS), such as the separation for 24 hr, have been known to be resulted in abnormal behavior, reduced volume of the hippocampus, neurogenesis, decreased interneurons and GABA level (Barbosa Neto et al, 2012;Daskalakis et al, 2014;Delpech et al, 2016;Fabricius, Wörtwein, & Pakkenberg, 2008;Figueiredo et al, 2016;Hays et al, 2012;Oitzl, Workel, Fluttert, FroÈsch, & Ron de Kloet, 2000;Schmidt, Okimoto, Dent, Gordon, & Levine, 2002;Schmidt et al, 2004;Wei et al, 2015). Since the purpose of this study is to examine the immediate effects of MS on the development of the GABA system in the hippocampus, we used MS for 24 hr on P4.…”
Section: Maternal Separationmentioning
confidence: 99%